Ni-foam based heterogenous Bi2S3 polyhedrons/multi walled carbon nanotubes (Bi2S3@MWCNTs/NF) as an advanced battery type electrode for enhanced supercapacitor performance - Philips O. Agboola; Imran Shakir; Zeyad Ammar Almutairi; Sahar Saad Shar; Mohamed F. Aly Aboud (Journal of Materials Research and Technology, 2023)
In current study, we report the hydrothermal synthesis of highly electroactive bismuth trichloride (Bi2S3) polyhedrons, modified with multi walled carbon nanotubes (MWCNTs). The physiochemical characterizations of pure Bi2S3 and Bi2S3@MWCNTs composite were carried out through X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, and scanning electron microscopy (SEM). XRD data revealed orthorhombic crystal structure of Bi2S3 having crystallite size of ∼13.23 nm, that got reduced to ∼10.81 for Bi2S3@MWCNTs composite. Polyhedral Bi2S3 showed some tendency to aggregate after fabricating with MWCNTs. Functional group analysis confirmed the formation of Bi–S bonds through multiple metal-sulfide bonding vibrations in the finger print region (880–550 cm−1). For electrochemical tests, Bi2S3/NF and Bi2S3@MWCNTs/NF were applied as electrodes. Due to the synergistic effects from highly conductive MWCNTs and pseudo-active Bi2S3, as prepared Bi2S3@MWCNTs/NF exhibited a significant enhancement in electrochemical response. The specific capacity of Bi2S3@MWCNTs/NF was measured as 625.1 C g−1, that was ∼1.45 times greater than that of non-fabricated Bi2S3 polyhedrons. Additionally, Bi2S3@MWCNTs/NF delivered a better charge/discharge efficiency. The values of RES (2.25 Ω) and RCT (3.54 Ω) prominently decreased for Bi2S3@MWCNTs/NF due to low internal and diffusional resistance.